PENGGUNAAN E-COMMERCE PADA UKM UNTUK MENINGKATKAN KINERJA PERUSAHAAN - Susan Rachmawati (Universitas Bina Sarana Informatika, 2012)
E-commerce is one way that can be done by companies to improve corporate performance in terms of marketing, sales, promotion (publicity) and others. Means that you can use can use a blog or a website using free or paid hosting. By using this e-commerce company / ukm can make sales anywhere and anytime without the cost of marketing, promotion and even paying the salaries of employees to market and sell products, because all this is still an obstacle for small and medium businesses are limited funds available to conduct marketing , promotion and sale of goods. The method used in this paper is the author of the secondary data can be through a variety of reference, namely books, internet, journals, etc. that support the writing of this Keywords: e-commerce, performance, ukm